Neck-Tongue Syndrome: Viewpoints on Etiology in a Patient with Bilateral Symptoms - Jonathan S. Sidlow; Mark J. Raden; Richard Sidlow (Case Reports in Neurological Medicine)
Neck-Tongue Syndrome is a rare entity, and when it presents in the pediatric age group, it is usually due to osseous, ligamentous, or nervous anatomic variation. We present below a case involving a patient whose bilateral symptoms were intermittently present from the age of five to the age of twenty-one years and discuss this case in light of the present theories of the anatomic substrate underlying this syndrome.